Characterization and wear performance of CrAgN thin films deposited on Cr-V ledeburitic tool steel - Jurči, Peter (Materiali in tehnologije, 2014)
Specimens made from Vanadis 6 cold-work tool steel were machined, ground, heat processed using a standard regime and finally mirror polished. After that they were layered with CrAgN. The Ag-content in the layers was chosen to be inmass fractions w = 3 % and 15 %. Microstructural analyses revealed that the CrN grew in a columnar manner. The addition of 3 % Ag did not influence the manner of growth of the films, but the addition of 15 % Ag made considerable changes to the film growth. Both the hardness and the Young's modulus were not influenced by the incorporation of 3 % Ag, but the addition of 15 % Ag reduced them. The layers with 3 % Ag had excellent adhesion on the steel substrate. On the other hand, the addition of 15 % Ag had a very negative impact on the coating adhesion. The films with the addition of 3 % Ag had superior tribological properties against hard material (alumina) as well as against a soft counterpart (CuSn6 as-cast bronze), while those with 15 % Ag were too soft and they underwent intensive wear.
Keywords: orodna jekla; ledeburitno jeklo; tanke plasti; kromov nitrid; tribologija